2023
DOI: 10.14715/cmb/2023.69.15.40
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized low-density lipoprotein induces M2-type differentiation of macrophages to promote the protracted progression of atherosclerotic inflammation in high-fat diet-fed ApoE -/- mice

Bo Zhang,
Weichang Xia,
Jingqun Zhou
et al.

Abstract: In this study, the significance of oxidized low-density lipoprotein (ox-LDL) in promoting the progression of atherosclerosis was investigated by inducing the differentiation of macrophages into the M2 subtype within a high-fat diet-induced ApoE -/-mouse model. The study also evaluated the effects of β2-AR agonists and blockers on this process. Ox-LDL was found to have significantly promoted the differentiation of macrophages into the M2 type and induced related functional alterations. Furthermore, it activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 48 publications
0
10
1
Order By: Relevance
“…Considering that lipids persist within plaques without being removed, our research group concluded that a vicious cycle occurs during atherosclerosis progression involving recruitment and differentiation of M1-type macrophages into M2like phenotypes followed by phagocytosis and subsequent death processes. This cycle perpetuates itself by recruiting more M1-type macrophages for differentiation into M2-like phenotypes followed by phagocytosis and death (Zhang et al, 2023) (see Figure 2).…”
Section: Lipid-induced Macrophage Differentiation Towards M2-like Phe...mentioning
confidence: 99%
See 4 more Smart Citations
“…Considering that lipids persist within plaques without being removed, our research group concluded that a vicious cycle occurs during atherosclerosis progression involving recruitment and differentiation of M1-type macrophages into M2like phenotypes followed by phagocytosis and subsequent death processes. This cycle perpetuates itself by recruiting more M1-type macrophages for differentiation into M2-like phenotypes followed by phagocytosis and death (Zhang et al, 2023) (see Figure 2).…”
Section: Lipid-induced Macrophage Differentiation Towards M2-like Phe...mentioning
confidence: 99%
“…4.2 β-AR receptor blockers, via β2-AR, inhibit lipid-induced macrophage differentiation from M1-like phenotype to M2-like phenotype and inhibit atherosclerosis progression (Zhang et al, 2023) Our previous study demonstrated that β2-AR stimulators can enhance the effects of ox-LDL on macrophage function. However, metoprolol, propranolol (Smith and Teitler, 1999;Hoffmann et al, 2004;Baker, 2005) and ICI118551, which exhibit varying degrees of selectivity for β2-AR, can transduce signals through β2-AR and inhibit the effects of ox-LDL on macrophage function.…”
Section: Exploration Of Evidence-based Medical Evidence Mechanisms Fo...mentioning
confidence: 99%
See 3 more Smart Citations